Strategic Planning Process in A Implemented of National Strategic Area Spatial Plans in Terms of Water and Soil Conservation - Madya, Faizal (Indonesian Association for Public Administration (IAPA), 2024)
Democratization raises the equal rights of people in utilizing space and environment to improve their welfare. This article gives the idea that a National Strategic Area Spatial Plans can be implemented and can improve community welfare. This can be done through a strategic planning process(Oden, 1999) which consists of: (1) finding and re-understanding what are the main functions and tasks of the organization. (2) analyze the environment outside the organization to further determine the values that are beneficial to the interests of the community. (3) analyze the internal environment of the organization to find out the strengths and weaknesses of the organization in facing changes and developments in the use of space that is currently happening. (4) fulfilling values that are beneficial to the interests of the community in accordance with the capabilities and authority of the organization. Methodology –This article is based on a qualitative research design and using data from in-depth interviews with informants involved in the implementation of national strategic area spatial plans at Puncak Bogor Regency, data updates were carried out from January to June 2024. The results of the study show that there are two things that can support the success to improve community welfare in implemented National Strategic Area Spatial Plans. the Strategic Planning Process can work when supported by the leadership attitude. This leadership attitude support by creating a work atmosphere can develop creative ideas and employee innovations. Secondly, the Strategic Planning Process is successful when supported by an open system organizational structure. Includes only the results obtained by the author(s) of the solution to the problems posed in the study of interest. The presence of diagrams, graphs, and tables illustrating the research.